Handbook of non-motor symptoms in Parkinson's Disease - Chaudhuri, K Ray.; SpringerLink (Online service). (London New York Springer, 2011)
Handbook of Non-Motor Symptoms in Parkinson's Disease is designed to provide practical tips and emphasize key priorities for treatment of non-motor aspects of the disorder. The quick-reference handbook format, with key points highlighted by the use of figures and tables, will provide the reader with high-value practical information.
Introduction -- The burden of non-motor symptoms -- Assessing non-motor symptoms: an overview of scales and questionnaires -- An in-depth look at the Non-Motor Symptom Scale -- Neuropsychiatric symptoms -- Sleep-related symptoms -- Bladder dysfunction -- Sensory symptoms -- Sexual symptoms -- Gastrointestinal symptoms -- Other symptoms.
Electronic reproduction.
Keywords: Parkinson's disease -- Diagnosis -- Handbooks, manuals, etc; Parkinson's disease -- Pathophysiology -- Handbooks, manuals, etc; Parkinson Disease; Electronic books